A Potential Approach for Enhancing Carbon Sequestration During Peatland Restoration Using Low-Cost, Phenolic-Rich Biomass Supplements - Alshehri, Adel; Dunn, Christian; Freeman, Chris; Hugron, Sandrine; Jones, Timothy G.; Rochefort, Line (Frontiers in Environmental Science, 2020)
The addition of phenolic compounds to peatland soils has been proposed as a means of enhancing the suppression of enzymes, reducing the rate of organic matter decomposition and increasing below-ground carbon sequestration. This study evaluated the potential of phenolic enrichment as a peatland restoration strategy by adding wood chips from common tree species to peat substrate and determining the impacts on key components of organic matter decomposition and Sphagnum growth. All treatments tended to increase the concentration of phenolics and suppress the activities of β-glucosidase (measured as an indicator enzyme that plays a key role in cellulose decomposition), significantly so with the Spruce (Picea mariana) and Cedar (Thuja occidentalis) wood chips mixed into the peat. All substrate additions to the peat tended to reduce fluxes of carbon dioxide (CO2) and significantly more so with surface additions of Spruce and Larch (Larix laricina) wood chips. The addition of woodchips per se, had no detrimental effect on Sphagnum growth for any of the treatments. These results indicate that through the addition of phenolic compounds to peatlands, it may be possible to inhibit extracellular enzyme activities in order to reduce the flux of CO2 from soils to the atmosphere. Thus, organic soil conditioning could reduce the carbon footprint for commercial activities such as Sphagnum culture.